(untitled) (Bangladesh Journal of Botany, 2018)
This present work deals with monitoring some molecular aspects standing beyond the varied production of volatile oil in three medicinal plants (Ocimum basilicum, B, Mentha longifolia, M and Origanum majorana, O) after ten days of exposure to drought stress by using 250 mM mannitol as a drought inducer. The results showed that proline has increased in all drought-stressed plants as compared to the control. Four protein bands (210, 70, 63 and 18 kDa) have disappeared in stressed B-plant, in addition to low molecular weight newly expressed protein bands (16-78 kDa). The protein polymorphism has varied among the species and ranged from 16.66 to 54.54%. RAPD-DNA technique indicated high similarity of genomic-DNA in stressed and unstressed plants. GC-MS screened intensive fluctuations within the pool of phytochemical compounds. The genomic DNA structure was generally stable under drought stress despite of new proteins expression which mediated the induction of chemical compounds with antioxidant property to cope with the drought stress.